EFFECTS OF ASCORBIC ACID AND SUGAR ON PHYSICAL, TEXTURAL AND SENSORY PROPERTIES OF COMPOSITE BREADS - Simic, Marijana (Food and Feed Research, 2021)
The present study was carried out to demonstrate the combined effects of different maize flour, ascorbic acid and sugar on the physical, textural and sensory properties of composite breads. The composite flour was prepared using 70% of wheat flour and 30% of flour obtained from grain of differently coloured maize - light blue, blue, red and yellow maize flour. Chemical characterization of composite flours made with four different types of maize was also assessed. Furthermore, the content of total phenolics, flavonoids, anthocyanins, phenolic acids and antioxidant capacity in composite flours was determined. The total of 12 breads that were prepared, four of which were control composite breads, four breads with ascorbic acid, and four were breads with ascorbic acid and sugar. The content of total phenolic compounds showed clear differences among all composite flours. The anthocyanins content determined in composite flours was in the following descending order: blue>red>light blue, while in the yellow maize composite flour anthocyanins were not detected. The results showed that the addition of AsA (0.025%) and sugar (5%) negatively affected the volume as well as the specific volume of composite wheat-maize breads. The texture analysis showed that the addition of AsA in amount of 0.025% had no impact on springiness, cohesiveness and resilience of bread crumb, while it increased crumb hardness. However, composite breads made with AsA and AsA and sugar showed a more compact structure, with a larger number of cells and smaller mean cell areas. Bread samples with AsA and sugar in the tested doses had the lowest springiness, which is indicative of brittleness and reflects the tendency of the bread to crumble when slicing. Results of the sensory evaluation revealed that the AsA and sugar addition had a generally positive effect on the investigated sensory attributes.